A note about Volterra operators on weighted Banach spaces of entire functions. Issue 11 (21st March 2015) - Bonet, José; Taskinen, Jari
Abstract : We characterize boundedness, compactness and weak compactness of Volterra operators V g acting between different weighted Banach spaces H v ∞ ( C ) of entire functions with sup‐norms in terms of the symbol g ; thus we complement recent work by Bassallote, Contreras, Hernández‐Mancera, Martín and Paul3 for spaces of holomorphic functions on the disc and by Constantin and Peláez16 for reflexive weighted Fock spaces.